2011
DOI: 10.1021/om200843f
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Complexes of κ(P)- and κ(P)-η6-Coordinated KITPHOS Monophosphines: Efficient Catalysts for the Direct Ortho Arylation of 2-Phenylpyridine andN-Phenylpyrazole with Aryl Chlorides

Abstract: Thermolysis of the P-coordinated KITPHOS monophosphine complex [(p-cymene)RuCl2(KITPHOS)] in chlorobenzene at 120 °C resulted in displacement of the p-cymene to afford [{κ(P)-η6-KITPHOS}RuCl2], the first example of a constrained-geometry complex in which the κ(P)-bonded diphenylphosphino group and the η6-coordinated proximal phenyl ring are connected by an unsaturated two-carbon tether; both complexes form efficient catalysts for the direct ortho arylation of 2-phenylpyridine and N-phenylpyrazole with a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 89 publications
2
26
0
Order By: Relevance
“…Here, phosphines with pendant aromatic groups in close proximity to the phosphorus atom are predominantly used as polydentate ligands for the formation of tethered ruthenium complexes. 1826 Utilizing the chelate effect to stabilize the arene–metal interaction is one major benefit of tethered complexes compared to nontethered complexes. 21,27 In the case of chiral ligands, another advantage is a restrained stereochemical situation which raises the racemization barrier of the chiral tethered complex.…”
Section: Introductionmentioning
confidence: 99%
“…Here, phosphines with pendant aromatic groups in close proximity to the phosphorus atom are predominantly used as polydentate ligands for the formation of tethered ruthenium complexes. 1826 Utilizing the chelate effect to stabilize the arene–metal interaction is one major benefit of tethered complexes compared to nontethered complexes. 21,27 In the case of chiral ligands, another advantage is a restrained stereochemical situation which raises the racemization barrier of the chiral tethered complex.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Doherty et al [25] reported the application of [{κ(P)-6 -KITPHOS}RuCl 2 ] (KIT-PHOS = 11-Dicyclohexylphosphino-12-phenyl-9,10-ethenoanthracene, and in fact this was obtained by thermolysis of the P-coordinated KITPHOS monophosphane complex [(pcymene)RuCl 2 (KITPHOS)] in chlorobenzene at 120 ∘ C) for the selective mono-ortho-arylation of 2-phenylpyridine and N-phenylpyrazole. The reaction conditions entailed heating the 2-phenylpyridine and N-phenylpyrazole with a variety of aryl chlorides in the presence of 2.5 mol% of the catalyst at 120 ∘ C in NMP for 24 h. The selected reaction afforded the monoarylated product, but some diarylated product was also obtained.…”
Section: Directed Metalating Group (Dmg)-assisted C(sp 2 )-H Activatimentioning
confidence: 99%
“…Doherty et al achieved the selective monoarylation of 2-phenylpyridine and phenylpyrazoles using ruthenium(II) catalysts, [RuCl 2 (p-cymene)(PPh 2 L)], which gave predominantly monoarylated products with a minor or insignificant amount of diarylated products (Scheme 9) [55]. The reaction gave 76% of monoarylation and 9% diarylation with chlorobenzene as the arylating agent.…”
Section: Ruthenium-catalysed Selective Monoarylationmentioning
confidence: 99%